Preserving Vocal Health in Student Teachers - Froemming, Gina (My University, 2015)
Teachers and student teachers are at risk for developing voice disorders due the intense vocal requirements necessary for teaching (Cultiva, Vogel & Burdorf, 2013; Roy et al., 2004; Van Lierde et al., 2009). Due to the negative impact voice disorders have on the lives and vocational capabilities of teachers, preventative measures should be taken to preserve vocal functioning from the early stages of student teaching (Schneider & Bigenzahn, 2004). Ten student teachers from a Midwestern university participated in this study. Seven were women and three were men. The mean age was 25 with a range of 21 ? 26. Participants were all student teaching through the duration of the study period, had no history of a voice disorder, and were not former or current smokers. Participants were randomly assigned to one of two treatment groups. The study was a between group and within group comparison using a modified ABACA crossover design comparing the effectiveness of vocal hygiene and vocal functional exercises. Additionally, a visual analysis of perceptual measures was completed. Acoustic, perceptual and self-rated measures were collected prior to participants? student teaching, six weeks into student teaching, and 14 weeks into student teaching. Results revealed that while both vocal hygiene and vocal functional exercises resulted in some vocal improvements and prevented a decline in many measures, vocal functional exercises resulted in greater positive outcomes in acoustic, perceptual and self-rating measurements. The results indicated that vocal functional exercises should be introduced into the routines of student teachers early in their careers in order to produce the greatest positive outcomes and to best preserve healthy vocal functioning during the student teaching experience.